2006
DOI: 10.1177/003335490612100417
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Care Adequacy in Three Provinces of Vietnam: Long an, Ben Tre, and Quang Ngai

Abstract: Vietnam has high numbers of maternal and infant mortality and morbidity. Each year, 1,500 women die and 45,000 others become disabled as a result of pregnancy and childbirth complications. 1 There were 37,700 neonatal deaths in Vietnam in 1999. 2 The maternal mortality rate is 165 per 100,000 live births 3 and the infant mortality rate is around 30 per 1,000 live births. 4,5 Antenatal care (ANC) has been proven to be effective in preventing pregnancy adverse outcomes. 6 For ANC to be effective, women should ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 12 publications
3
42
3
Order By: Relevance
“…Moreover, minorities usually have their own languages, which makes it difficult to communicate with health educators, leading to a lack of knowledge about ANC. Educational level was also correlated with the time of first ANC attendance, as observed in other studies in Vietnam [21] and in other countries [19,32,33]. Women with a higher level of education are more likely to appreciate the importance of early entry than the less educated ones.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Moreover, minorities usually have their own languages, which makes it difficult to communicate with health educators, leading to a lack of knowledge about ANC. Educational level was also correlated with the time of first ANC attendance, as observed in other studies in Vietnam [21] and in other countries [19,32,33]. Women with a higher level of education are more likely to appreciate the importance of early entry than the less educated ones.…”
Section: Discussionsupporting
confidence: 69%
“…A widely-used model in numerous studies exploring the usage of health care services is the Andersen Health Seeking Behavior model [20]; it has also been particularly used in several studies on ANC [17,21,22]. Nonetheless, there is limited information on the factors related to late entry into ANC in Vietnam and a theoretical health seeking behavior model as a framework for the analysis of these related factors has not yet been published.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of smoking were lost when the models were adjusted for the other socio-demographic factor. Previous studies have shown that smokers practice less healthy care behaviors in general and in prenatal care in particular [33,34]. On the contrary, it seems that among Nepali women smoking does not play a significant role in participation in prenatal care.…”
Section: Discussionmentioning
confidence: 85%
“…A woman was classified as having adequate use of ANC if she visited an ANC clinic at least three times during the course of her pregnancy, with the initial visit taking place within the first four months of the pregnancy (Trinh, Dibley, and Byles 2006). A woman was considered as having received DC if her delivery was at a health facility under the supervision or assistance of a trained health professional.…”
Section: Variables Dependent Variablementioning
confidence: 99%